1988
DOI: 10.1111/j.1744-6570.1988.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Holistic Versus Decomposed Rating of Position Analysis Questionnaire Work Dimensions

Abstract: Recent studies have attempted to reduce the cost and intrusiveness of the Position Analysis Questionnaire (PAQ) by limiting the amount of information provided to the analyst, with consistently negative results. We examined an alternative technique for improving the cost-effectiveness of the PAQ that avoids the need to rate the hundreds of items that constitute the instrument. Three groups of raters (professional job analysts, graduate students in industrial psychology who were familiar with the PAQ, and PAQ-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Similarly, Sackett, Cornelius, and Carron (1981) found no differences in job classification results when using a comprehensive task analysis or a simplified paired-comparison procedure. However, Butler and Harvey (1988) found virtually no convergence between holistic ratings of Position Analysis Questionnaire dimensions and decomposed ratings of individual Position Analysis Questionnaire items.…”
Section: Differences Between Competency Ability and Task Statementsmentioning
confidence: 80%
“…Similarly, Sackett, Cornelius, and Carron (1981) found no differences in job classification results when using a comprehensive task analysis or a simplified paired-comparison procedure. However, Butler and Harvey (1988) found virtually no convergence between holistic ratings of Position Analysis Questionnaire dimensions and decomposed ratings of individual Position Analysis Questionnaire items.…”
Section: Differences Between Competency Ability and Task Statementsmentioning
confidence: 80%
“…In these instances their holistic ratings might well diverge from ratings of each GWA produced via a detailed, decomposed-judgment process (Gibson et al, 2004). Additional studies demonstrated poor convergence between single-item ratings and decomposed scores in rating situations that were quite similar to the O*NET (for example, Butler and Harvey, 1988;DeNisi and Shaw, 1977;Harvey et al, 1994). Indeed, when the high cognitive demands inherent in the holistic judgment strategy are combined with the nebulous nature of the O*NET GWA ''operational definitions'', such divergence may be further exacerbated.…”
Section: The O*netmentioning
confidence: 99%
“…Based on prior research (Butler and Harvey, 1988;Harvey et al, 1994), we hypothesized that incumbents would produce inflated holistic ratings relative to analysts, and that low holistic-decomposed GWA convergence would be seen. The common-metric questionnaire (CMQ) was selected to provide the decomposed-judgment GWA scores in view of:…”
Section: Convergence Of Holistic Vs Decomposed Gwa Ratingsmentioning
confidence: 99%
“…Evaluation of comprehensive methods relative to quality criteria: The PAQ (M cCormick et al 1969), AET (Rohmert and Landau 1983), and the Job Pro® le method (W agner 1985 ) represent the three most complete comprehensive methods based on extent of use, scope, and depth of analysis. Of these methods, the PAQ (M cCormick et al 1969) has been most often studied in terms of the quality criteria (M cCormick et al 1977, 1978, Colbert and Taylor 1978, Taylor and Colbert 1978, M cCormick 1979, Hoyos 1981, Shaw and Riskan d 1983, Cornelius et al 1984, Friedm an and Harvey 1986, Harvey and Hayes 1986, Carter and Biersner 1987, Butler and Harvey 1988, Sparrow 1989, M urphy 1991, M urphy et al 1991. The three comprehensive methods are evaluated according to criteria described by both Carm ines and Zeller (1979) and Petitti (1994) in table 5.…”
mentioning
confidence: 98%